Dampak Pertumbuhan Ekonomi, Penanaman Modal Asing, Populasi, dan Konsumsi Energi terhadap Emisi Karbon Dioksida di Enam Negara ASEAN Selama Periode 2000-2021 - Yohanes Berchman Suhartoko; Monica Gede Dewinta Ekaristi (Society, 2023)
The increase in CO2 emissions has led to a rise in global temperatures. The rising CO2 emissions in ASEAN need further examination concerning the variables influencing this increase. This study aims to test and obtain empirical evidence on the determinants of CO2 emissions in six ASEAN countries (Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam) during the period 2000–2021. The factors considered in this study include Economic Growth (GGDP), Foreign Direct Investment (FDI), Total Population (POP), Fossil Energy Consumption (EF), and Renewable Energy Consumption (GET). This research employs panel data regression using both time series and cross-sectional data. The Chow and Hausman tests were conducted to determine the appropriate model, and the fixed-effect model was selected as the best fit. This research demonstrates that GET has an insignificant relationship with CO2 emissions, whereas GGDP, FDI, POP, and EF have significant relationships with CO2 emissions. In conclusion, considering all the independent variables in this study that affect CO2 emissions, future efforts should focus on finding ways to control these variables to reduce CO2 emissions.